A Gender-Based Communication Approach to Hasten the Prevention of Stunting in Bojonegoro Regency - Maranditya, Berliananda; Andarwati, Siti; Ruslanjari, Dina (Universitas Negeri Yogyakarta, 2025)
The gender-based stunting prevention acceleration program in Bojonegoro Regency still faces challenges. Therefore, this study aims to analyze the communication strategy for accelerating stunting prevention through a gender perspective. A descriptive method with a qualitative approach was used in the study, conducted in three sub-districts (Kapas, Balen, and Gondang) from January to December 2023. Primary data were collected through in-depth interviews with 23 informants from various related agencies. Data analysis utilized source triangulation, technique triangulation, and GAP analysis. The results show that the stunting prevention acceleration program by the Bojonegoro Regency Government with a gender approach has been planned specifically and sensitively. However, only the Women's Empowerment, Child Protection, and Family Planning Agency have a gender-friendly program with balanced participation. Despite using detailed communication design through intrapersonal approaches, public communication, digital media, and the 8-convergence communication strategy design, the program still has gender participation gaps in access and decision-making.